PEREMPUAN DI DIREKSI, KEBANGSAAN, DAN KAPABILITAS: MAMPUKAH KOMITE AUDIT MEMBATASI AKUNTANSI KREATIF? FEMALE DIRECTORS, NATIONALITY, AND CAPABILITY: CAN AUDIT COMMITTEES CURB CREATIVE ACCOUNTING? - Riyan Hidayat; Nurmayanti, Poppy; Nasir, Azwir (Universitas Riau, 2025)
Creative accounting often used by managers to deceive financial statement users for personal gain, poses a threat to transparency and accountability. This study investigates the role of corporate governance in mitigating such practices, focusing on the influence of female board members, directors' nationality, and directors' capabilities, with the audit committee as a moderating variable. Using data from Indonesian manufacturing companies during 2019–2022, multiple linear regression and Moderated Regression Analysis (MRA) were employed. The findings reveal that the presence of female directors and the capabilities of board members significantly affect the level of creative accounting, while nationality does not. Furthermore, the audit committee does not moderate the relationship between female directors and creative accounting. Practically, these findings underscore the importance of enhancing gender diversity and leadership competence to reduce manipulative accounting behavior. Theoretically, this study contributes to the body of knowledge on corporate governance and financial reporting integrity. From a policy perspective, the results offer valuable insights for regulators and investors in promoting more transparent and accountable corporate financial disclosures.